Enhancing BTQ Learning Motivation Through Basic Nagham Art Training for Santri at Pesantren Darunnajah Jakarta - Sofwan Manaf; Rokimin; Muhammad Irfanudin Kurniawan; Anas Fauzi; Ahsanul Mufid (Universitas Darunnajah, Jakarta, Indonesia, 2025)
This study aims to examine the improvement of Baca Tulis Al-Qur'an (BTQ) learning motivation among santri at Darunnajah Islamic Boarding School through basic training in the art of nagham (Qur'anic rhythmic recitation). BTQ learning frequently suffers from low motivation because it is perceived as monotonous and purely technical, while existing literature has rarely examined the role of Qur'anic musical arts as an intrinsic motivational instrument. A qualitative approach with a classroom action research design was employed over two cycles, involving 32 santri at the junior level. Data were collected through participant observation, in-depth interviews, motivation questionnaires, and documentation, then analyzed using the Miles and Huberman interactive model. Data validity was ensured through source and method triangulation. The findings indicate that basic nagham training, comprising the introduction of the seven maqamat (bayati, shaba, hijaz, nahawand, rast, jiharka, and sika), breathing exercises, and talaqqi-musyafahah methods, significantly enhances santri learning motivation. Improvement is evident in four dimensions: intrinsic interest in BTQ learning (rising from 56% to 89%), learning persistence (62% to 91%), active engagement (58% to 87%), and fluency in reading the Qur'an. The study concludes that integrating the art of nagham into BTQ learning provides aesthetic-spiritual stimuli that simultaneously fulfill the psychological needs of autonomy, competence, and relatedness, thereby strengthening santri's intrinsic motivation and reading quality.